Kristal Hemoglobin pada Bercak Darah yang Terpapar Beberapa Gel Pembersih Tangan Antiseptik Berbasis Alkohol Menggunakan Tes Teichmann dan Tes Takayama - Erriza Yuni Elpia; Enikarmila Asni; Mohammad Tegar Indrayana (Jurnal Online Mahasiswa (JOM) Bidang Kedokteran, 2016)
ABSTRACTBloodstain found at the crime scene can be one of the evidences of criminal action. To diminish the evidences and traces, the criminal might clean and erase the bloodstain by using alcohol based antiseptic handsanitizer which often used by people in daily life. The bloodstain which is contaminated by the alcohol-based antiseptic handsanitizer could possibly affect the result of a bloodstain examination by using the Teichmann test and the Takayama test. This research had been done to observe the image of hemoglobin crystals on bloodstains that are exposed to alcohol-based antiseptic handsanitizers by using the Teichmann and Takayama test. In this research there are 5 types of alcohol-based antiseptic handsanitizer brands swabbed on to bloodstained slides for each test. The result shown on 22 slides (100%) had positive result. This conclude the hemoglobin crystals could still be found on bloodstains which exposed to alcohol-based antiseptic handsanitizer.Keywords: Bloodstain, hemoglobin crystals, alcohol-based antiseptic handsanitizer, Teichmann test, Takayama test.